160 The Neurosurgical Anatomy of Deficits in Speech Production. (April 2023) - Andrews, John P.; Cahn, Nathan; Speidel, Benjamin; Chung, Jason; Levy, Deborah; Wilson, Stephen; Berger, Mitchel S.; Chang, Edward
Abstract : INTRODUCTION: Why do similar neurosurgical lesions cause a range of deficits in speech production? We investigated Broca's aphasia as a disorder of fluency and apraxia of speech (AOS) as a disorder of articulatory coordination to dissociate the anatomy and lesional etiology of these syndromes. METHODS: Patients were prospectively tested with a standardized speech paradigm. Resections were outlined into 3D regions of interest and transformed into a common brainspace (MNI brain). Recordings of speech were retrospectively review by speech language experts to assess apraxia of speech. A voxel-based lesion-mapping (VLSM) algorithm was used to associate resection areas with acute postoperative aphasia or apraxia of speech. Averages of white-matter tracts were overlaid onto MNI reconstructions for analyses of white-matter tract involvement. Pre-operative diffusion tensor imaging reconstructions were created using peri-lesional regions of interest for seeds to investigate perilesional white matter tracts in these cohorts. RESULTS: Of 289 patients with left sided craniotomies and prospective language evaluation, 19 had Broca's aphasia. 255 of these patients had recordings available for expert review, of whom 28 had apraxia of speech. VLSM analysis found Broca's aphasia and fluency deficits were not associated with classic anatomic Broca's area (pars opercularis and triangularis). Rather, they were associated with ventral sensorimotor cortex (SMC) and supramarginal gyrus (P < 0.001). Apraxia of speech was associated the most ventral aspects of SMC (P < 0.001). SLF III reconstructions terminated in the areas associated with Broca's aphasia and fluency deficits, but had more limited overlap with the VLSM regions associated with apraxia of speech. CONCLUSIONS: Lesions leading to AOS and Broca's aphasia after neurosurgical resection do not correlate with Broca's area. Rather, they cluster in ventral sensorimotor cortex. Subcortical white-matter tract injury may explain disparate non-fluent aphasia subtypes in patients with anatomically similar lesions.